Investigação do potencial da celulose bacteriana no processo de imobilização da peroxidase do rabanete para descoloração de corantes - Santos, Camila Goes (2024)
The present study was focused on the immobilization of peroxidase extracted from radish and purified through a methodology based on a two-phase aqueous system. The determination of enzymatic activity was carried out using a spectrophotometric test based on the oxidation of guaiacol in tetraguaiacol, revealing a value of 1.133 U. As a support for the immobilization of the enzyme, bacterial cellulose obtained from Kombucha, a carbonated drink obtained from from the fermentation of green tea that contains bacteria capable of producing cellulose in the form of films. The enzyme was immobilized by the physical adsorption method using purified bacterial cellulose, without chemical modifications and immobilized by covalent bonding where the cellulose was subjected to oxidation to form aldehyde groups, by sodium periodate (NaIO4) at different times and concentrations of the oxidant, aiming at immobilizing the enzyme through Schiff base. The determination of the aldehyde content showed that bacterial cellulose was oxidized by 4% periodate time the 1h with a higher degree of oxidation (0.327mmol). The resulting membranes were characterized by thermogravimetric analysis (TG), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) and N2 adsorption/desorption, with determination of surface area, micropore volume and size distribution and diameters of the pores. The membranes containing peroxidase were also subjected to determination of enzymatic activity and protein determination, observing that there were no statistically significant differences between the activities of all samples. According to the results obtained in the characterizations, peroxidase immobilized by physical adsorption and immobilized by bacterial cellulose oxidized by 4% sodium periodate time the 1h were chosen for discoloration tests of solutions of the cationic dyes methylene blue, crystal violet and rhodamine 6G and the anionic dye synthetic indigo. The discoloration of the solutions was monitored by a UV/VIS spectrophotometer. The dye solution that showed the highest degree of discoloration was crystal violet, being respectively 91.53% for peroxidase immobilized by pure bacterial cellulose and 91.18% for peroxidase immobilized by bacterial cellulose oxidized by 4% sodium periodate time the 1 hour. Therefore, the results indicate that immobilized radish peroxidase has the potential for dye decolorization and that the decolorization performance of the enzyme immobilized by physical adsorption or covalent bodwas similar